Zellweger spectrum disorder patient–derived fibroblasts with the PEX1‐Gly843Asp allele recover peroxisome functions in response to flavonoids. Issue 3 (26th October 2018) - MacLean, Gillian E.; Argyriou, Catherine; Di Pietro, Erminia; Sun, Xuting; Birjandian, Sara; Saberian, Panteha; Hacia, Joseph G.; Braverman, Nancy E.
Abstract: Zellweger spectrum disorder (ZSD) results from biallelic mutations in PEX genes required for peroxisome biogenesis. PEX1‐G843D is a common hypomorphic allele in the patient population that is associated with milder disease. In prior work using a PEX1‐G843D/null patient fibroblast line expressing a green fluorescent protein (GFP) reporter with a peroxisome‐targeting signal (GFP‐PTS1), we demonstrated that treatments with the chemical chaperone betaine and flavonoid acacetin diacetate recovered peroxisome functions. To identify more effective compounds for preclinical investigation, we evaluated 54 flavonoids using this cell‐based phenotype assay. Diosmetin showed the most promising combination of potency and efficacy (EC50 2.5 µM). All active 5′, 7′‐dihydroxyflavones showed greater average efficacy than their corresponding flavonols, whereas the corresponding flavanones, isoflavones, and chalcones tested were inactive. Additional treatment with the proteostasis regulator bortezomib increased the percentage of import‐rescued cells over treatment with flavonoids alone. Cotreatments of diosmetin and betaine showed the most robust additive effects, as confirmed by three independent functional assays in primary PEX1‐G843D patient cells, but neither agent was active alone or in combination in patient cells homozygous for the PEX1 c.2097_2098insT null allele. Moreover, diosmetin treatment increased PEX1, PEX6, and PEX5 protein levels in PEX1‐G843D patient cells, but none of these proteins increased in PEX1 null cells. We propose that diosmetin acts as a pharmacological chaperone that improves the stability, conformation, and functions of PEX1/PEX6 exportomer complexes required for peroxisome assembly. We suggest that diosmetin, in clinical use for chronic venous disease, and related flavonoids warrant further preclinical investigation for the treatment of PEX1‐G843D–associated ZSD. Abstract : To identify preclinical leads for treated Zellweger spectrum disorder, we evaluated 54 flavonoids using a PEX1‐G843D patient cell line. Diosmetin showed the most promising combination of potency and efficacy by several measures. We propose that diosmetin acts as a pharmacological chaperone that improves the stability, conformation, and functions of PEX1/PEX6 exportomer complexes required for peroxisome assembly.